2022
DOI: 10.3389/fimmu.2022.874056
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ligand-Receptor Pairs Associated With Tumour Characteristics in Clear Cell Renal Cell Carcinoma

Abstract: The tumour microenvironment (TME) of clear cell renal cell carcinoma (ccRCC) comprises multiple cell types, which promote tumour progression and modulate drug resistance and immune cell infiltrations via ligand-receptor (LR) interactions. However, the interactions, expression patterns, and clinical relevance of LR in the TME in ccRCC are insufficiently characterised. This study characterises the complex composition of the TME in ccRCC by analysing the single-cell sequencing (scRNA-seq) data of patients with cc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Overexpression of CX3CL1 is typically associated with improved prognosis because of its ability to modulate the body’s immune response. Liu et al discovered that CX3CL1 might exert an anti-tumorigenic effect on the KIRC cells line, hence contributing to the clinical benefit ( Liu et al, 2022 ). Tsaur and his colleagues demonstrated that renal cells carcinoma of the chromophobe subtype had considerably reduced CX3CL1 gene expression relative to normal tissue, and that CX3CR1 and C-reactive protein were positively correlated ( Tsaur et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of CX3CL1 is typically associated with improved prognosis because of its ability to modulate the body’s immune response. Liu et al discovered that CX3CL1 might exert an anti-tumorigenic effect on the KIRC cells line, hence contributing to the clinical benefit ( Liu et al, 2022 ). Tsaur and his colleagues demonstrated that renal cells carcinoma of the chromophobe subtype had considerably reduced CX3CL1 gene expression relative to normal tissue, and that CX3CR1 and C-reactive protein were positively correlated ( Tsaur et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…High EMT enrichment scores on bulk RNA sequencing are associated with worse disease specific survival in ccRCC 22 , and various EMT ligand-receptor pairs have been implicated. 23, 24,25 Prior spatial transcriptomic work using spot-based resolution has also identified EMT-rich tumor cells being associated with worse prognosis in the TCGA cohort. 26 Still, specific ligand-receptor pairs from the EMT pathway were not elucidated in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…So far, various studies have provided conflicting results regarding the role of CX3CL1 in anti-tumor immunity. Recent studies have suggested that signaling through the ligand-receptor pair formed by CX3CL1 and its receptor CX3CR1 may improve the prognosis of ccRCC patients [ 38 ]. However, in another new clinical trial, the chemokine CX3CL1 was associated with shorter PFS in metastatic triple-negative breast cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%